2021
DOI: 10.1002/ptr.7185
|View full text |Cite
|
Sign up to set email alerts
|

Effects of resveratrol on female reproduction: A review

Abstract: The present review summarizes the current knowledge concerning physiological effects of resveratrol (RSV) with emphasis on the RSV action on female reproductive processes. The review outlines provenance, properties, mechanisms of action, physiological and therapeutic actions of RSV on female reproduction and other physiological processes, as well as areas of possible application of R. This review is based on the search for the related full papers indexed in Medline/Pubmed, Web of Science and SCOPUS databases b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 89 publications
0
4
0
Order By: Relevance
“…Therefore, resveratrol levels may be translated, via SIRT1, into the development of inflammation, regulation of apoptosis, mitochondrial function, and protection from oxidative stress. Among other reasons, sirtuin has become a therapeutic target in reproductive system diseases [ 28 ]. Mitochondrial activity, as well as the efficiency of the organization of cell organelles, is one of the keys to achieving good-quality oocytes.…”
Section: Interaction Between Sirt1 and Resveratrolmentioning
confidence: 99%
“…Therefore, resveratrol levels may be translated, via SIRT1, into the development of inflammation, regulation of apoptosis, mitochondrial function, and protection from oxidative stress. Among other reasons, sirtuin has become a therapeutic target in reproductive system diseases [ 28 ]. Mitochondrial activity, as well as the efficiency of the organization of cell organelles, is one of the keys to achieving good-quality oocytes.…”
Section: Interaction Between Sirt1 and Resveratrolmentioning
confidence: 99%
“…Resveratrol has stilbenoid chemistry which is produced by more than 70 species of plants in response to stress, injury, infection, or ultraviolet radiations ( Sirotkin, 2021 ). Resveratrol was found to have an apoptotic induction in uterine cancer cells.…”
Section: Natural Kinase Inhibitors For Management Of Endometrial/uter...mentioning
confidence: 99%
“…In females, resveratrol is considered a natural phytoestrogen since its chemical structure is similar to that of some estrogens, such as diethylstilbestrol. Although some publications have shown a negative influence of resveratrol on female reproductive processes [23], several studies have demonstrated beneficial effects of resveratrol. It has been shown to promote ovarian cell culture, in vitro fertilization of oocytes, ovarian stimulation, ovarian follicular growth and oocyte maturation, embryonic development, cryopreservation of oocytes and embryos, and it can improve the quality of oocytes obtained from aged females [24][25][26].…”
Section: Introductionmentioning
confidence: 99%